2020
DOI: 10.1186/s12887-020-02025-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of zinc sulfate on indirect hyperbilirubinemia in premature infants admitted to neonatal intensive care unit: a double-blind, randomized clinical trial

Abstract: Background: Hyperbilirubinemia is a common neonatal problem. Studies conducted on the effectiveness of zinc salts on serum indirect bilirubin levels in newborns have yielded different results, all calling for further research. This study aimed to determine the effect of oral zinc sulfate on indirect hyperbilirubinemia in preterm infants admitted to the neonatal intensive care unit. Methods: A randomized double-blind clinical trial was performed in the neonatal intensive care unit of Vali-e-Asr Hospital in Birj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…the nding of our study in the bene cial effect of Zn in preterm neonate in decreasing the serum bilirubin levels was agreed with some studies which found signi cant decrease in serum bilirubin levels in preterm infants who were given Zn supplementation if compared with those who did not receive Zn supplementation [14].…”
Section: Discussionsupporting
confidence: 92%
“…the nding of our study in the bene cial effect of Zn in preterm neonate in decreasing the serum bilirubin levels was agreed with some studies which found signi cant decrease in serum bilirubin levels in preterm infants who were given Zn supplementation if compared with those who did not receive Zn supplementation [14].…”
Section: Discussionsupporting
confidence: 92%
“…These findings followed previous animal studies which showed that zinc supplements reduced TSBR [30]. Zinc has been shown to increase bowel movements and therefore bilirubin fecal excretion, which in turn reduces the enterohepatic circulation of bilirubin [29]. We speculate that the earlier supplementation of zinc from fortification may also have allowed to the F80 group to manage bilirubin excretion more efficiently.…”
Section: Discussionsupporting
confidence: 88%
“…Zinc is another constituent of nutrient supplement that has been demonstrated to improve bilirubin elimination. A recent randomized, double blind trial demonstrated that neonates between 31 and 36 weeks gestation requiring phototherapy, had significantly reduced jaundice within 48 h of receiving oral zinc [29]. These findings followed previous animal studies which showed that zinc supplements reduced TSBR [30].…”
Section: Discussionsupporting
confidence: 70%
“…Supplementation of a suspension of fenofibrate and vitamin D, E, and C during white light therapy significantly reduced bilirubin levels and the duration of phototherapy in neonates [76]. The administration of oxaliplatin in combination with fluro-pyrimidine/folinic acid and monoclonal antibody, and supplementation of zinc sulfate syrup and Yinzhihuang oral liquid during phototherapy are also effective for reduction of bilirubin in neonates [77][78][79].…”
Section: Recent Advancements In the Treatment Of Hyperbilirubinemiamentioning
confidence: 99%